Β-Patchoulene represses hypoxia-induced proliferation and epithelial-mesenchymal transition of liver cancer cells. Issue 5 (2nd May 2022) - Tu, Huahua; Wang, Wei; Feng, Yanqing; Zhang, Linfei; Zhou, Huadong; Cheng, Caitao; Ji, Lei; Cai, Qinghe; Feng, Yong
ABSTRACT: Hepatocellular carcinoma (HCC) is a malignant tumor originating from liver epithelial cells with a high clinical mortality rate. β-Patchoulene (β-PAE) is a compound extracted from patchouli, which has analgesic, anti-inflammatory and antioxidant effects. This research aims to probe the impacts of β-PAE on hypoxia-induced HCC cell proliferation and epithelial-mesenchymal transition (EMT). Firstly, hypoxic injury models were constructed in HCC Huh-7 and MHCC97 cells, and the hypoxic injury cell models were then treated with different concentrations of β-PAE. The cell viability, proliferation, migration, invasion and apoptosis were checked by the cell counting kit-8 (CCK-8) assay, colony formation assay, Transwell assay, flow cytometry and terminal deoxyribonucleotide transferase (TdT)-mediated dUTP nick end labeling (TUNEL) assay. The expression of Survivin protein, EMT markers and the NF-κB/HIF-1α pathway was gauged by Western blot (WB) or cellular immunofluorescence or reverse transcription-polymerase chain reaction (RT-PCR). The in-vivo experiment was conducted to confirm the anti-tumor role of β-PAE. As a result, β-PAE abated hypoxia-induced HCC cell growth, proliferation, migration, invasion and EMT and facilitated apoptosis in vitro and in vivo dose-dependently. Further mechanism studies displayed that β-PAE inactivated the NF-κB/HIF-1α pathway, and HIF-1α activation significantly reversed the β-PAE-mediated tumor inhibition. β-PAE repressed the proliferation and EMT of hypoxia-induced HCC cells by choking the NF-κB/HIF-1α pathway, suggesting that β-PAE was a potential drug for HCC treatment. Graphical Abstract: uf0001